Territorialidades emergentes en el periurbano platense - Nieto, Daniela Patricia (Gran La Plata, 2022)
Emerging Territorialities in the peri-urban area of La Plata. This book compiles articles focused on the different emerging territorialities shaped by the primary activities of agricultural production in the peri-urban area of La Plata district. This territory is a space affected by economic logics permeated by a series of particular practices and social relations that have been established by social agents over time. Taking into account the forms of production and the activities derived from them in the peri-urban area, the chapters discuss the production of cut flowers; horticultural production mostly in greenhouses; life in the communities of Italian, Portuguese, Japanese and Bolivian migrants who have territorialized the area creating spatial mediations in order to take root in the place; and, in turn, all the problems derived from certain dynamics linked to the activities generated by a mostly migrant population that has settled for years on the periphery of the city.